An integrated model with interval valued neutrosophic sets for the selection of lean and sustainable suppliers - (:unkn) unknown (Springer Verlag, 2020)
Suppliers have a very important role in the supply chain (SC) and accordingly the evaluation and selection of the supplier is quite significant. The aim of this study is to develop a hybrid methodology for the determination of the best supplier considering lean and sustainable factors. However, the selection of sustainable suppliers often includes indeterminate, inconsistent and vague information due to the subjective nature of individual decisions. Interval-valued neutrosophic sets (IVNSs) have a considerable capability to deal with indeterminacy and vagueness in the decision-making process. To this end, we integrated two strong decision making tools, ANP and TODIM, under interval valued neutrosophic sets environment. Firstly, IVN-ANP was employed to calculate the criteria weights. Further, obtained weights are utilized in the IVN-TODIM method as an input for the best sorting of the alternatives. A numerical example was introduced to illustrate the applicability and efficacy of the proposed approach. © 2020, Springer Nature Switzerland AG.
Keywords: IVN-ANP; IVN-TODIM; Lean and sustainable supplier